Altered Patterns of Maternal Behavior Transitions in Rats Exposed to Limited Bedding and Nesting Material Paradigm - Grace E. Pardo; Lucero B. Cuevas; Luis F. Pacheco‐Otalora; Enver M. Oruro (Brain and Behavior, 2024)
ABSTRACT Introduction Maternal care plays a fundamental role in early life, and the alteration of its patterns can negatively affect the developmental course of the offspring in a myriad of domains in both rats and humans. The limited bedding and nesting (LBN) protocol is an extensively used paradigm in rodents to address the impact of altered maternal behavior patterns on infants' neurodevelopment. Here, we explore the altered patterns of maternal care in rats in LBN conditions by describing sequences of transition between maternal behavior components using network analysis. Using this technique, we capture how often maternal behavior transitions take place during the LBN period and which behaviors play central roles in those transitions over time. Materials and Methods Female rats and their pups were placed in standard and LBN housing conditions from Postpartum Days 2 to 9, during which maternal behavior was observed during the light and dark phases. We used inferential statistical analysis to compare the maternal behavior profiles of control and LBN dams, and network analysis was used to capture the altered sequence of maternal behavior transitions during the period of LBN. Results Compared to control dams, LBN dams significantly increased their high crouch nursing posture during light/dark phases (p = 0.018), and the number of behavioral transitions increased only during the dark phase (p = 0.0004). Network analysis revealed specific altered patterns of behavioral transitions in LBN dams, characterized by the predominance of switches between active nursing postures during the first five days of the LBN protocol. Conclusion Nursing behavior was the most disrupted component of maternal behavior under the LBN protocol, mainly during the dark phase. Network analysis can complement and extend traditional methods to gain a more thorough understanding of maternal care strategies and behavioral patterns in LBN conditions and potential consequences for the offspring.